ASSESSMENT FOR STUDENTS 21 st CENTURY SKILLS - Boboyev , Maqsud Mahmudovich (Educational Research in Universal Sciences, 2023)
The development of society, reforms in the field of education in our country require highly educated and knowledgeable candidates in accordance with the world standard. This article describes the solution of the problems in the fields of physics and the problem of prospects for improvement.